Dinamika Komunikasi Bisnis Digital dalam Kampanye Marketplace di Media Sosial: Analisis Interaksi Pengguna Berbasis Social Network Analysis - Widiya Avianti; Hilman Abdurrahman; Pupu Sri Andriyani; Intan Yuniar Putri Sukanda; Iseu Nur Latifah (MAMEN: Jurnal Manajemen, 2026)
Digital transformation in the trade sector has encouraged marketplaces to utilize social media as a primary medium for business communication and marketing activities. Promotional campaigns such as discounts, free shipping, shopping vouchers, and flash sales are widely used strategies to attract consumer attention and increase user engagement within the online shopping ecosystem. This article aims to analyze how digital business communication is implemented in marketplace marketing campaigns on social media, identify communication barriers that occur, and understand patterns of user interaction in digital conversations. The study employs a qualitative descriptive approach using Social Network Analysis and NVivo software to process data from social media conversations related to marketplace promotional campaigns. The analysis reveals that user discussions are dominated by price promotion themes, particularly discounts and free shipping, which play a major role in attracting consumer interest. In addition, consumer trust and shopping experience emerge as important factors that strengthen user engagement in digital interactions. These findings indicate that the effectiveness of business communication in marketplace marketing depends not only on promotional intensity but also on the platform’s ability to build consumer trust and provide a positive shopping experience within the digital commerce ecosystem.